Pemberdayaan Masyarakat Melalui KKN Stain Madina Pada Desa Gunung Tua Julu Kabupaten Paluta - Ade Khadijatul Z Harahap; Azizah Nur; Imam Syafi’I; Khairul Riski Ahmad; Nur Holizah; Nurhalisa Khairani; Sahnan Batubara; Shelly Madinah; Silfi Khoiriyah Lubis; Wahdini Wahdini (Jurnal Kabar Masyarakat, 2024)
Real Work Lectures (KKN) can be said to be a way of student service to society. The service method is carried out in several stages, including observation and site visits to obtain information on abilities that can be developed and problems that must be resolved. Batang Onang is a sub-district in Indonesia, located in North Padang Lawas Regency, North Sumatra Province. The STAIN Madina KKN Student Program includes activities that have been discussed and accepted by the village so they are easy to carry out. The activities carried out include community empowerment and improving the quality of education and religion. Because the research carried out was carried out in Gunung Tua Julu Village. The conclusion that can be drawn from the STAIN Madina Real Work Lecture activities is that you should be smart in contributing to society because every human being will essentially return to society and it is also a good place to socialize in society. Based on research results obtained from data in the field, this research is still less than perfect and needs to be improved further.